Compact for care: how the Affordable Care Act marketplaces fell short for a vulnerable population in Hawaii. Issue 11 (29th November 2021) - Ng Kamstra, Joshua S; Molina, Teresa; Halliday, Timothy
Abstract : The Patient Protection and Affordable Care Act (ACA) was passed in 2010 to expand access to health insurance in the USA and promote innovation in health care delivery. While the law significantly reduced the proportion of uninsured, the market-based protection it provides for poor and vulnerable US residents is an imperfect substitute for government programs such as Medicaid. In 2015, residents of Hawaii from three Compact of Free Association nations (the Federated States of Micronesia, Palau and Marshall Islands) lost their eligibility for the state's Medicaid program and were instructed to enrol in coverage via the ACA marketplace. This transition resulted in worsened access to health care and ultimately increased mortality in this group. We explain these changes via four mechanisms: difficulty communicating the policy change to affected individuals, administrative barriers to coverage under the ACA, increased out of pocket health care costs and short enrolment windows. To achieve universal health coverage in the USA, these challenges must be addressed by policy-makers.